Platform YouTube sebagai Sarana Dakwah Masa Kini: Kontribusi Habib Jafar - Warliah, Wiwin; Yahya Auliya’ Abdillah; Ahmad Mirzaq Miftahul huda (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This research examines the utilization of YouTube as a medium for da'wah by Habib Husein Ja'far Al Hadar, who manages to deliver religious messages with an approach relevant to modern audiences, especially the younger generation. Through the case study method and qualitative approach, this research observes how Habib Jafar utilizes YouTube's interactive features to build active engagement, such as through comments and question and answer sessions. Habib Jafar's preaching is not only informative but also contextualized, where he connects Islamic teachings to relevant social issues such as tolerance, social justice, and peace. This innovation, through visual illustrations and graphic effects, makes the da'wah content more interesting and easy to understand. The results showed that Habib Jafar's approach received a positive response from the audience. Most of the comments contain appreciation, questions, and sharing of personal experiences, creating an active dialog space among the audience. This indicates that da'wah through YouTube allows da'wah to be flexible, reach audiences without time or place restrictions, and create a closer emotional connection with audiences. In conclusion, social media, especially YouTube, has proven to be an effective and inclusive da'wah platform in the digital era. It not only expands the reach of da'wah but also increases the closeness and engagement between preachers and audiences, making it a relevant da'wah solution in the midst of rapid social change.